2012
DOI: 10.1615/intjmedmushr.v14.i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Actin Cytoskeleton Enhanced Cytokine Synthesis of Splenocytes Stimulated with Beta-Glucan from the Cauliflower Medicinal Mushroom, Sparassis crispa Wulf.:Fr. (Higher Basidiomycetes) in Vitro

Abstract: Beta-glucan (BG) is a representative pathogen-associated molecular pattern (PAMP) produced by pathogenic fungi. SCG is a BG obtained from Sparassis crispa, which stimulates splenocytes in DBA/2 mice to produce cytokines, such as GM-CSF, IFN-γ, and TNF-α. In the present study, we analyzed the molecular mechanism of SCG-mediated cytokine synthesis using cytocharasin D (CytD), an inhibitor of actin polymerization. It was found that GM-CSF and TNF-α synthesis of splenocytes stimulated with SCG, but not with lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In another study, the dried mushroom Flammulina velutipes was milled and submitted to aqueous and alkaline extractions, and then the crude b-glucan residue was subjected to further alkaline extraction at 100 8C, using 2% and then 25% KOH (Smiderle et al, 2006). b-Glucan from mushroom Sparassis crispa was prepared using cold alkali (10% NaOH/5% urea) at 4 8C with a 2-day extraction time, and subsequently the extract was applied to a DEAE Sephadex A25 column for further purification (Shibata et al, 2012). Sen et al (2013) also used distilled water (100 8C) to extract b-glucan from a hybrid mushroom, pfls1h of P. florida and L. squarrosulus (Mont.)…”
Section: Purification Of Mushroom B-glucanmentioning
confidence: 99%
“…In another study, the dried mushroom Flammulina velutipes was milled and submitted to aqueous and alkaline extractions, and then the crude b-glucan residue was subjected to further alkaline extraction at 100 8C, using 2% and then 25% KOH (Smiderle et al, 2006). b-Glucan from mushroom Sparassis crispa was prepared using cold alkali (10% NaOH/5% urea) at 4 8C with a 2-day extraction time, and subsequently the extract was applied to a DEAE Sephadex A25 column for further purification (Shibata et al, 2012). Sen et al (2013) also used distilled water (100 8C) to extract b-glucan from a hybrid mushroom, pfls1h of P. florida and L. squarrosulus (Mont.)…”
Section: Purification Of Mushroom B-glucanmentioning
confidence: 99%
“…Shibata et al found that both GM-CSF and TNF- α synthesis in DBA/2 mouse splenocytes stimulated with SCG, but not with lipopolysaccharide, were significantly enhanced in the presence of cytochalasin D (CytD), an inhibitor of actin polymerization [27]. On the other hand, Kim et al pointed out the importance of the role of Toll-like receptor 4 (TLR4) [28].…”
Section: Chemical Constituents and Bioactive Components Of S Crismentioning
confidence: 99%
“…Sparassis crispa is an edible mushroom that contains high amounts of β-glucan, more than 30% of the dry weight of the fruiting bodies, compared with levels in other mushrooms [6]. Several studies have revealed that consumption of S. crispa and β-glucan extracted from S. crispa has immunopotentiative effects, such as enhanced inflammatory cytokine production in splenocytes, improved peripheral NK cell activity, and anti-tumor action [6,7,8,9]. Based on these results, S. crispa consumption enhances immune function.…”
Section: Introductionmentioning
confidence: 99%